#TITLE_ALTERNATIVE# - KOMANG PARINATA (NIM : 10210015), I
In physics there are a lot of data that is included in the stochastic system, in this study used the data of stock price fluctuations as the data that has stochastic system. The data used is the closing price of shares of six companies, Bank Negara Indonesia(BBNI),Bank Rakyat Indonesia(BBRI),Bank MANDIRI(BMRI) which include in bluechips stocks category and Bank Danamon(BDMN),Bank Tabungan Negara(BBTN),Bank CMIB Niaga(BNGA)whichs include in non bluechips stocks.In this research conducted prediction closing price of IHSG by Support Vector Regression(SVR).Support Vector Machine (SVM) is an algorithm which based on Vapnik statistical model. Support Vector Regression (SVR) is one of many SVM developments. While SVM is used in for solving clustering problem, SVR is used in regression problem. For this experiment, SVR will be used for predicting stock closing price in Indonesian Stock Market (IHSG). Three bluechips and three non-bluechips banking stocks will be used to compare their stability when we use them in simulation for predicting their closing prices. WEKA (Weikato Environment for Knowledge Analysis) is used for simulating SVR algorithm. Two kernel functions polynomial RBF(Radial Basis Function) and Polynomial will be used and their performance will be compared.